Study of English sounds: phonetics and phonology in action - Ceramella, Nick (Revista Leitura, 2019)
What justification might there be foi an essay on phonetics and phonology? After all, there is already a plethora of books on the subject. However, most of them are highly academic in their approach, provide a detailed initiation into this particular area of language study and tend to be as technical as lengthy. Of course, they serve their purpose well, but can be daunting to the neophyte. This essay then is meant to cover the need for a more general and gradual introduction to such a complex area of the study of English. I simply intend to supply a support to the more academically oriented introductions to phonetics, thus preparing the conceptual ground. This is a summary overview of the main features of this area of linguistics: its scope and principles of enquiry, its key concepts and basic issues. These are expressed and explained in such a way to make them as accessible as possible to people who have no prior knowledge or expertise in the subject. Yet, allow me to say that however simple my approach may be, it is not simplistic. The idea is to give students an inicial familiarity with the fascinating and challenging world of sounds "in action' , and to encourage them into close critical exploration where the issues might not be readily accessible. DOI: 10.28998/0103-6858.2005v2n36p147-181